Evaluation of veterinary students’ knowledge, attitudes, and practices towards food safety in Salvador, Brazil - Stephanie Macedo Dias; Marciara de Souza Cardoso; Rafael Sepúlveda Fonseca Trevisan Passos; Brenno Guimarães Barreto; Mauricio Costa Alves da Silva; Carlos Pasqualin Cavalheiro (Revista Brasileira de Saúde e Produção Animal)
ABSTRACT Foodborne diseases (FBDs) constitute a significant health problem worldwide, and unhealthy food handling practices cause their transmission in the population. There is limited information on food safety knowledge, attitudes, and practices (KAP) among veterinary students worldwide. This was the first study to address KAP on food safety among veterinary students in Brazil. Data from 226 students were collected through an online questionnaire that included four sections: demographic characteristics, knowledge, attitudes, and practices. High levels of food safety knowledge (17.77) and attitudes (16.82) were found; however, food safety practices (10.62) were average. The results showed that most students had satisfactory food safety knowledge (100%) and good food safety attitudes (99.12%). However, 56.64% of the students had good food safety practices. Gender and marital status influenced food safety attitudes, while age influenced all attributes. Both years of study and food safety training affected food safety knowledge and attitude. It was found that students with more years of study and those who had already taken food safety courses had higher mean scores for these attributes. Training should be emphasized to strengthen food safety practices among students.